2016
DOI: 10.48550/arxiv.1612.03089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transition from Fireball to Poynting-flux-dominated Outflow in Three-Episode GRB 160625B

Abstract: The ejecta composition is an open question in gamma-ray bursts (GRB) physics 1 . Some GRBs possess a quasi-thermal spectral component in the time-resolved spectral analysis 2 , suggesting a hot fireball origin. Others show a featureless non-thermal spectrum known as the "Band" function 3-5 , consistent with a synchrotron radiation origin 5,6 and suggesting that the jet is Poynting-flux-dominated at the central engine and likely in the emission region as well 7,8 . There are also bursts showing a subdominant th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 33 publications
(71 reference statements)
3
32
0
Order By: Relevance
“…In principle, stronger constraints on coefficients for Lorentz violation could be derived by including the higherenergy photons detected by the Fermi Large Area Telescope (LAT). However, the LAT data are much sparser in terms of photon number, and there are only ten > 1 GeV LAT photons during the second sub-burst of GRB 160625B (Zhang et al 2016). This makes it challenging to extract the LAT-band light curve with high temporal resolution and requires additional assumptions in the error analysis beyond those adopted here.…”
Section: Constraints On Sme Coefficientsmentioning
confidence: 98%
See 1 more Smart Citation
“…In principle, stronger constraints on coefficients for Lorentz violation could be derived by including the higherenergy photons detected by the Fermi Large Area Telescope (LAT). However, the LAT data are much sparser in terms of photon number, and there are only ten > 1 GeV LAT photons during the second sub-burst of GRB 160625B (Zhang et al 2016). This makes it challenging to extract the LAT-band light curve with high temporal resolution and requires additional assumptions in the error analysis beyond those adopted here.…”
Section: Constraints On Sme Coefficientsmentioning
confidence: 98%
“…Its redshift is z = 1.41 (Xu et al 2016). This gamma-ray burst is special because its gamma-ray light curve consists of three dramatically different isolated sub-bursts with very high photon statistics (Burns 2016;Zhang et al 2016). Since the second sub-burst of GRB 160625B is extremely bright, its light curve in different energy bands can be readily extracted.…”
Section: Constraints On Sme Coefficientsmentioning
confidence: 99%
“…Interestingly, the Fermi/LAT was also triggered by this burst at T 0 + 188.54 seconds (Dirirsa et al 2016), and more than 300 photons with energy above 100 MeV were detected. The highest photon energy is about 15 GeV (Dirirsa et al 2016;Zhang et al 2016b). This GRB triggered GBM again at T 0 + 660 seconds.…”
Section: Data Reductionmentioning
confidence: 99%
“…Its prompt γ-ray lightcurve is composed of three episodes: a short precursor, a very bright main emission episode, and a weak emission episode. The three episodes emission are separated by two long quiescent intervals (Zhang et al 2016b). Interestingly, Zhang et al (2016b) found that a pure thermal spectral component and non-thermal spectrum (known as Band function; Band et al 1993) are existed in the precursor and main emission episodes, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation